SPIRITUAL EDUCATION IN THE ERA OF GLOBALIZATION (Proceedings of International Educators Conference, 2023)
Educating the growing young generation on the basis of religious and national values, strengthening the feeling of loyalty to their people and the Motherland in their hearts, warning them against the informational attacks of various destructive forces, proper protection, spiritual education and about cyberbullying.